Two-dimensional nano-channel film based on molecular encapsulation technology regulation and control, preparation and application

By using cucurbitol to encapsulate barium ions in graphene oxide nanofiltration membrane for interlayer adjustment, the problem of poor stability of the membrane in organic solvents is solved, higher permeability and retention performance are achieved, and the stability of long-term operation is maintained.

CN119549003AActive Publication Date: 2025-03-04NANJING TECH UNIV +2
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411697066.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-04
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing graphene oxide nanofiltration membranes have poor stability in organic solvents, are prone to swelling and compaction, and have poor retention and solvent permeability, making it difficult to maintain screening performance during long-term operation.

Method used

The interlayer adjustment of graphene oxide is made by using supramolecular cucumber urea to encapsulate barium ions, and the formation of ordered channels is promoted through interlayer cross-linking, thereby improving the stability and screening performance of the film.

Benefits of technology

The stable separation performance of graphene oxide film is achieved, the permeability of organic solvents and dye retention performance are improved, and the stable performance of long-term operation is maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549003A_ABST
    Figure CN119549003A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional nano-channel membrane based on molecular encapsulation technology regulation and control, and preparation and application thereof, and belongs to the technical field of nano-filtration membrane preparation. The graphene oxide film is constructed on the basis of a method for performing intercalation by encapsulating guest metal ions through subject supramolecules, and specifically, a substrate film is subjected to cross-linking modification, so that a GO selection layer on a substrate shows good dispersity, and it is guaranteed that the GO selection layer and the substrate have good binding force; and mixing the host-guest complex solution formed by packaging with the GO dispersion liquid to obtain a coating liquid, and uniformly depositing the coating liquid on a substrate by adopting a pressure-assisted filtration method to obtain the GO nanofiltration membrane. Through interlayer crosslinking, formation of more ordered channels is promoted, and meanwhile, the membrane is endowed with good stability and screening performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanofiltration membranes, and in particular to a two-dimensional nanochannel membrane regulated based on molecular encapsulation technology, and its preparation and application in screening dye molecules. Background Art

[0002] With the rapid development of the pharmaceutical, petrochemical and catalytic industries, the demand for organic solvents is increasing. In this context, a large amount of organic waste liquid must be properly treated. Direct discharge into the environment is not only a serious waste of resources, but also causes environmental harm. In the long run, it is extremely necessary to separate and recycle organic solvents.

[0003] Organic solvent nanofiltration (OSN) is a new type of membrane separation technology that can efficiently separate organic solvents and solutes with a relative molecular mass of 200 to 1000. Compared with conventional separation technologies, OSN has the advantages of low energy consumption, mild operating conditions and strong solvent recovery capabilities, and performs well in the recovery and purification of organic solvents. However, the main challenge faced by OSN membranes in practical applications is poor stability, easy swelling and compaction in solvents. Developing OSN membranes that are stable in various solvents and have good retention rates and solvent permeability is an issue that needs to be urgently addressed.

[0004] Graphene oxide (GO) is a two-dimensional material with tunable nanochannels. It has good film-forming properties and rich oxygen-containing functional groups, and is often made into separation membrane materials. Graphene oxide membranes are formed by stacking graphene oxide nanosheets through hydrogen bonds and π-π interactions. Their interlayer channels are easily affected in liquid environments and generally have poor stability in polar solvents because their oxygen-containing functional groups dehydrogenate and form negative charges when solvated, causing the layered microstructure to swell and disintegrate, significantly reducing the screening performance of the membrane during long-term operation.

[0005] Research has found that intercalation is an effective strategy to solve the swelling problem of GO and improve its stability. The strong interaction between the intercalant and the GO nanosheets adjusts the interlayer spacing while helping to maintain the stability of the interlayer structure of the GO membrane, so that the membrane can achieve continuous and stable separation. Technicians have tried to intercalate GO using ions, nanoparticles of different dimensions, molecules of different sizes, etc., such as metal cations, silica nanoparticles, and polystyrene. Although the various intercalants added to GO nanosheets can enhance the channel structure between layers to a certain extent, thereby improving the permeability of the membrane, the distribution of these intercalants is difficult to balance, making the transport channels irregular and unstable. Therefore, we need a cross-linking agent that can effectively adjust the interlayer spacing of GO and promote the formation of regular and ordered channels.

[0006] Cucurbituril 6 (CB6) is a cyclic supramolecule with polar carbonyl ports and hydrophobic cavities. Its rigid structure and nanoscale molecular size make it suitable as an intercalant for regulating the interlayer channels of GO. Since CB6 has a strong host-guest recognition ability and can bond with cations through ion-dipole interactions, CB6 can be used to encapsulate metal cations and then regulate the interlayer channels of GO, thereby constructing a two-dimensional material membrane with stable separation performance. In fact, the application of CB6 in the membrane field has shown that it has great development potential in improving permeability and precise design of membrane structure. For example, a cucurbituril / metal ion cross-linked graphene oxide composite membrane disclosed in Chinese patent CN 112934004 B uses a cucurbituril / metal ion supramolecular complex as a cross-linking agent, which not only improves the stability of the graphene oxide membrane in an aqueous environment, but also improves the permeability of the membrane as a rapid mass transfer channel for water molecules. However, the membrane structure disclosed in the application is essentially a water-permeable membrane rather than a nanofiltration membrane. Although it improves the permeation flux and selectivity for water molecules and can be used for pervaporation of butanol-water solution systems, it does not demonstrate its ability to retain dye solutes, which may be related to the base material used and the selected cross-linking metal ions. Summary of the invention

[0007] The purpose of the present invention is to solve the problems existing in the prior art, provide a graphene oxide organic solvent nanofiltration membrane and disclose its preparation process, utilize supramolecular cucurbituril to encapsulate barium ions to form a host-guest complex to regulate the GO screening channel, promote the formation of more ordered channels through interlayer crosslinking, and at the same time give the membrane good stability and screening performance.

[0008] In order to achieve the above technical objectives, the present invention is implemented by the following technical solutions:

[0009] A two-dimensional nanochannel membrane regulated by molecular encapsulation technology comprises a substrate and a selective separation layer on the substrate, wherein the selective separation layer is composed of graphene oxide (GO) nanosheets and also comprises a host-guest complex composed of cucurbituril encapsulated metal ions between adjacent GO nanosheets.

[0010] The cucurbituril is one or more of CB6, CB7, CB8, CB9, and CB10; the metal ion is Ba 2+ , Ca 2+ or Cu 2+ One or more of the .

[0011] The substrate is a polyimide material.

[0012] The surface of the substrate is cross-linked with polyamine, and the polyamine is selected from one of triethylenetetramine, diethylenetriamine and polyethylenepolyamine.

[0013] The method for preparing the above-mentioned two-dimensional nanochannel membrane comprises the following steps:

[0014] The metal ion salt and cucurbituril are dissolved in deionized water to encapsulate to form a host-guest complex solution, and a GO dispersion is added to obtain a coating solution. The coating solution is deposited on the modified substrate by a pressure-assisted filtration method to form a uniform coating layer, and a nanofiltration membrane is obtained after heat treatment.

[0015] The substrate is polyimide, which is firstly subjected to cross-linking treatment. The cross-linking treatment process is: immersing the PI substrate in polyethylene polyamine with a mass concentration of 8-15% for 10-20 minutes to complete the cross-linking.

[0016] The metal ion salt is Ba 2+ , Ca 2+ or Cu 2+ Salt, whose anion is Cl - 、NO3 - 、CO3 2- 、SO4 2- Any one of .

[0017] The mass percentage of the metal ion salt in the host-guest complex solution is 0.2-0.5wt%, and the mass percentage of the cucurbituril is 0.6-0.8wt%.

[0018] GO dispersion is prepared by dispersing GO solution in deionized water and ultrasonically treating it for 100 to 140 min. The concentration of GO in the obtained GO dispersion is 0.03 to 0.05 mg mL -1 .

[0019] The volume ratio of GO dispersion to host-guest complex solution is 10:1-2.5.

[0020] The present application also discloses a two-dimensional nanochannel membrane prepared by the above method, wherein the obtained two-dimensional nanochannel membrane is obtained by adjusting the GO screening channel by using a host-guest complex formed by encapsulating a metal ion salt with cucurbituril. Through interlayer crosslinking, the formation of a more ordered channel is promoted, and at the same time, the membrane is endowed with good stability and screening performance.

[0021] The above-mentioned organic solvent nanofiltration membrane can be used in the separation and recovery of organic solvents, for example, dyes can be intercepted, and the dyes here can refer to one or more of reactive blue 19 (RB19), aniline blue (AB), methyl blue (MB), fast green (FG) and Coomassie brilliant blue (BBR).

[0022] The prepared product in this application achieved 27.23L m -2 h -1 bar -1The acetonitrile permeability was excellent, and 99.21% retention of Fast Green in acetonitrile was achieved while maintaining stable performance after 110 hours of continuous operation.

[0023] The beneficial effects of the present invention are:

[0024] 1. This application uses the host supramolecular cucurbituril to encapsulate the guest metal ions, and the host-guest complex intercalation method is used to construct the graphene oxide membrane, which promotes the formation of more ordered channels through interlayer crosslinking, and at the same time gives the membrane good stability and screening performance;

[0025] 2. The membrane prepared in this application has orderly and stable two-dimensional interlayer channels, showing good solvent permeability and dye retention performance; compared with GO membrane, its permeability to organic solvents is nearly doubled, and it has good organic solute removal ability; specifically, it achieved 27.23L m -2 h -1 bar -1 The acetonitrile permeability was excellent, and the retention of Fast Green in acetonitrile was 99.21%, while the performance remained stable after 110 hours of continuous operation.

[0026] 3. The addition of the encapsulated host-guest complex will affect the non-covalent bonding interaction between adjacent GO nanosheets. The metal ions in the host-guest complex interact with GO through cation-π interactions, which makes the GO sheets more orderly nano-stacking during the pressure-assisted process, thus making the membrane surface structure flatter. In addition, the micropore defects generated by loose stacking will be reduced, and more regular channels will shorten the solvent molecule transmission path, resulting in an increase in permeability.

[0027] 4. Nanofiltration membranes have controllable interlayer d spacing, which can effectively screen dye molecules by size exclusion;

[0028] 5. The nanofiltration membrane exhibits compressive resistance and long-term separation stability, which is mainly attributed to the rigid structure of CB6, which helps to inhibit the swelling of GO nanosheets, thereby enhancing the stability of the membrane;

[0029] 6. This application provides a new material for the intercalation of GO membranes and a new idea for constructing GO membranes with orderly and stable nanochannels. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Panel a shows the UV absorption spectra of 0.025M different salt solutions and GO suspension (50mg / L) mixed in a volume ratio of 1:1; Panel b shows the infrared spectra of GO and GO cationic membrane; Panel c shows the schematic diagram of the interaction between GO and metal ions and between CB6 and metal ions; Panel d shows the ITC isotherm of BaCl2 and CB6 complexation;

[0031] Figure 2 The small picture in middle a is GO-CB6-Ba 2+ Schematic diagram of membrane preparation process; b is CB6, GO membrane, GO-Ba 2+ Membrane and GO-CB6-Ba 2+ FTIR spectra of the membrane; c is GO membrane, GO-Ba 2+ Membrane and GO-CB6-Ba 2+ XPS full spectrum of the film; d panel is GO-CB6-Ba 2+ Ba 3d spectra of the films;

[0032] Figure 3 The middle and ac pictures are GO film and GO-Ba 2+ Membrane and GO-CB6-Ba 2+ Surface field emission scanning electron microscope (SEM) images of the membrane; df panels are GO membrane, GO-Ba 2+ Membrane and GO-CB6-Ba 2+ SEM cross-sectional images of the membrane; the insets gi and gi are GO membrane, GO-Ba 2+ Membrane and GO-CB6-Ba 2+ AFM images of the membrane;

[0033] Figure 4 The middle a panel shows the dry and wet GO membranes and GO-Ba 2+ Membrane and GO-CB6-Ba 2+ The interlayer spacing of the membrane; the b panel shows the changes in relaxation time of different membranes under the action of water molecule probes, and the ce panels are GO membrane, GO-Ba 2+ Membrane and GO-CB6-Ba 2+ Schematic diagram of membrane channel formation in the membrane;

[0034] Figure 5 Panel a shows the permeability of different membranes in different organic solvents; Panel b shows the permeability of GO-CB6-Ba 2+ The pressure resistance of the membrane in acetonitrile and water; Panel c reflects the relationship between the solvent permeability of different membranes and the solvent properties; Panel d shows the surface charge density of different membranes; Panel e is the dynamic water contact angle of different membranes; Panel f reflects the changes in the low-field NMR relaxation time of different membranes under the acetonitrile probe;

[0035] Figure 6 The small picture in middle a shows GO-CB6-Ba 2+ The separation performance of the membrane for different dyes in acetonitrile; panel b shows GO-CB6-Ba 2+ Long-term separation performance of membranes for Fast Green in acetonitrile. DETAILED DESCRIPTION

[0036] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the essence of the present invention, modifications and substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0037] In order to solve the problem of irregular transport channels caused by disordered stacking of GO sheets, the present application uses the cation-π interaction between metal ions and GO to help GO sheets to perform more orderly nanostacking. However, since both CB6 and GO have interactions with metal cations, the cross-linking ions are first screened.

[0038] 1) Screening of cross-linking ions based on the interaction between GO and metal cations

[0039] The UV absorption spectra of GO and GO in LiCl, NaCl, CaCl2, CuCl2 and BaCl2 solutions are shown in Figure 1 In the middle panel a, the characteristic peak of GO is at ~230nm, which is attributed to the π-π* aromatic conjugated double bond. Compared with the UV intensity of GO in pure water, the peak intensity of GO in various salt solutions is significantly reduced, indicating that the π-π* aromatic conjugated double bond of GO is greatly affected in various salt solutions, that is, there is a cation-π interaction ( Figure 1 (Small picture in middle c). Figure 1 In the middle panel b, the infrared spectra of GO and GO cationic membranes show the stretching of C=O, carboxyl CO, and aromatic C=C. Compared with the pure GO membrane, the carboxyl CO peak is red-shifted, indicating that the carboxylic acid group is coordinated with the cation, that is, there is an electrostatic interaction ( Figure 1 The C=C peak also has a red shift, indicating that cations generate cation-π interactions with GO sheets.

[0040] Different salt solutions were mixed with GO dispersion. After 2 h, the monovalent cation solution (Li + and Na +) and GO did not change significantly. However, the GO sheets in the GO dispersion to which the divalent cation solution was added agglomerated. This result occurs because, although metal cations with smaller ionic radius have a stronger ability to attract the π electron cloud of the benzene ring, their hydration energy in aqueous solution is also much higher than that of metal cations with larger ionic radius. Higher hydration energy means that metal cations can be highly solvated in aqueous solution and are therefore surrounded by a large number of water molecules, thereby providing a strong shielding effect to prevent metal ions from binding to GO nanosheets. Therefore, it is speculated that the interaction force between divalent cations and GO nanosheets is stronger than that between monovalent cations. Further verification was performed by calculating the binding percentage of GO with metal cations. The mixture of GO and metal cations was centrifuged, and the supernatant was subjected to ICP test with a reference metal salt solution of consistent concentration, and the content of metal ions bound to GO was reversely calculated. It was confirmed that the binding percentage of divalent cations to GO was greater than that with monovalent cations.

[0041] 2) Screening of cross-linking ions based on the interaction between metal ions and CB6

[0042] The binding strength of CB6 to metal ions is reflected by the binding constant. 2+ , Ca 2+ and Ba 2+ ) and CB6 showed a trend of increasing from small to large. Then, isothermal titration calorimetry was used to study the binding constants of CB6 and Ba 2+ Thermodynamics of interaction ( Figure 1 ΔH < 0, indicating that the reaction is driven by enthalpy. 2+ It interacts with CB6 through hydrogen bonds. -TΔS<0, indicating an entropy-driven process that produces conformational changes. ΔG<0, indicating that the reaction proceeds spontaneously. And Ba 2+ The ratio of the combination with CB6 is 2:1. So Ba was finally selected. 2+ As cross-linking ions for GO selective layer.

[0043] Example 1

[0044] This embodiment discloses a method for preparing a graphene oxide organic solvent nanofiltration membrane, introducing CB6 to encapsulate Ba 2+ The formed host-guest complex controls the interlayer of GO to solve the instability problem of GO membrane in organic solvents. The preparation process of the membrane is referenced Figure 2 In the small picture a, the specific steps are as follows:

[0045] 1) Preparation of polyimide (PI) substrate by non-solvent induced phase inversion method: The preparation of PI substrate can refer to the prior art. Specifically, PI is first placed in a vacuum oven at 70°C for overnight drying to remove moisture, and then dissolved in a mixed solution of N-methylpyrrolidone (NMP) and polyethylene glycol (PEG 400) at a certain concentration, stirred to form a homogeneous solution, and allowed to stand for degassing to form a casting solution, in which the contents of polyimide, PEG 400, and NMP are 30wt%, 20wt%, and 50wt%, respectively; the casting solution is poured on a polyethylene terephthalate non-woven fabric, and a 100-micron-thick scraper is used to evenly scrape it, and finally it is immersed in water to complete the phase inversion, thereby obtaining the initial PI substrate.

[0046] 2) PI substrate modification: The PI substrate was immersed in triethylenetetramine (TETA) with a mass concentration of 10% for 15 minutes for cross-linking. Polyimide contains a large number of amide groups. Triethylenetetramine is a polyamine with three amine groups, which can undergo amidation reaction with the amide groups in polyimide to form a cross-linked structure. The cross-linked PI substrate was immersed in deionized water to remove the residual cross-linking agent. The purpose of cross-linking is to make the PI substrate have a certain stability in organic solvents, so as to prepare a GO composite membrane with certain organic solvent separation performance. The reason for choosing a cross-linking time of 15 minutes is that the PI membrane with a cross-linking time of 15 minutes has the smallest weight loss ratio in NMP solvent.

[0047] 3) Preparation of GO dispersion: The GO solution was uniformly dispersed in deionized water and ultrasonicated for 120 min using an ultrasonic cell disruptor to remove large GO aggregates and promote the formation of a uniform GO dispersion. The concentration of GO in the resulting GO dispersion was 0.04 mg mL -1 .

[0048] 4) Preparation of GO nanofiltration membrane: BaCl2 (0.0037 g) was dissolved in 100 mL of deionized water, and CB6 (0.0075 g) was added. After the solution was completely dissolved, 12.5 mL of GO dispersion was added to obtain a coating solution. Using the pressure-assisted filtration method, 112.5 mL of the coating solution was deposited on the modified PI substrate (effective membrane area was 7.065 cm) at a pressure of 4 bar. 2 ) to form a uniform coating layer, and then heat treated at 60 °C for 1 h to obtain a GO nanofiltration membrane, which is denoted as GO-CB6-Ba 2+ The membrane is stored in deionized water or test solvent for future use.

[0049] Comparative Example 1

[0050] The difference between Comparative Example 1 and Example 1 is only in step 4): 12.5 mL of GO dispersion was added to 100 mL of deionized water to obtain a coating solution. Using a pressure-assisted filtration method, 112.5 mL of the coating solution was deposited on the modified PI substrate (effective membrane area of ​​7.065 cm 2 ) to form a uniform coating layer, and then heat-treat at 60°C for 1h to form a membrane. The prepared membrane product is recorded as GO membrane, and the membrane is stored in deionized water or test solvent for future use.

[0051] Comparative Example 2

[0052] The difference between Comparative Example 2 and Example 1 is only in step 4): BaCl2 (0.0037 g) was dissolved in 100 mL of deionized water, and after the dissolution was complete, 12.5 mL of GO dispersion was added to obtain a coating solution. Using a pressure-assisted filtration method, 112.5 mL of the coating solution was deposited on the modified PI substrate (effective membrane area of ​​7.065 cm 2 ) to form a uniform coating layer, and then heat-treated at 60°C for 1 h to form a film. The prepared film product is recorded as GO-Ba 2+ The membrane is stored in deionized water or test solvent for future use.

[0053] Comparative Example 3

[0054] The difference between Comparative Example 3 and Example 1 is only in step 4): CB6 (0.0075 g) was dissolved in 100 mL of deionized water, and after the solution was completely dissolved, 12.5 mL of GO dispersion was added to obtain a coating solution. Using a pressure-assisted filtration method, 112.5 mL of the coating solution was deposited on the modified PI substrate (effective membrane area of ​​7.065 cm 2 ) to form a uniform coating layer, and then heat-treated at 60°C for 1h to form a membrane. The prepared membrane product is recorded as GO-CB6 membrane, and the membrane is stored in deionized water or test solvent for later use.

[0055] Comparative Example 4

[0056] The difference between Comparative Example 4 and Example 1 is that the PI substrate is not cross-linked, and the other steps and processes are the same. Experiments have confirmed that after coating the uncross-linked PI substrate and the PI substrate cross-linked by TETA with the GO selective layer, it was found that the coating layer on the uncross-linked PI substrate was uneven, while the GO selective layer on the cross-linked PI substrate showed good dispersion, and the two had good bonding force.

[0057] Related performance tests

[0058] 1. GO membranes and GO-Ba prepared in Comparative Example 1, Comparative Example 2 and Example 1 2+ Membrane and GO-CB6-Ba2+ The FTIR spectrum of the film is shown in Figure 2 As shown in the middle panel b, GO-CB6-Ba 2+ The membrane retains the characteristic peaks of GO membrane and also contains the characteristic peaks of CB6 molecules. -1 (-OH), 1726cm -1 (-C=O), 1640cm -1 (C=C), 1364cm -1 (CO, carboxyl), 1232 cm -1 (CO, epoxy) and 1083cm -1 There is an obvious absorption peak at (CO, alkoxy). 1716cm -1 The vibration absorption peak of -C=O is 1470cm -1 The vibration absorption peak of CN at 955cm -1 The vibration absorption peaks of -CH at the membrane are all characteristic peaks of CB6 molecules. XPS results further prove that CB6 and Ba 2+ The successful introduction of Figure 2 The experiment confirmed that GO-Ba 2+ Membrane and GO-CB6-Ba 2+ The surface of the membrane is evenly distributed with barium, indicating that the Ba 2+ The presence of Ba 2+ In the case of GO-CB6-Ba 2+ The barium content on the membrane surface is less than that on GO-Ba 2+ This indicates that in the presence of CB6, CB6 binds to Ba 2+ The interaction between the two makes more Ba 2+ In the XPS Ba 3d spectrum of the film, the binding energy centered at 779eV and 795eV corresponds to Ba 3d, further indicating that GO-CB6-Ba 2+ Ba exists in the membrane 2+ ( Figure 2 (middle d inset).

[0059] 2. Effect of intercalation on the microstructure of GO membrane

[0060] from Figure 3 As can be seen from the small figures in Figure ac, the GO membranes and GO-Ba prepared in Comparative Example 1, Comparative Example 2 and Example 1 2+ Membrane and GO-CB6-Ba 2+The membrane surface of the membrane shows the obvious and unique ridge structure characteristics of GO membrane. The GO membrane shows a larger ridge structure, while the ridge characteristics of the GO membrane surface after intercalation modification become smaller, which may be due to Ba 2+ and CB6-Ba 2+ The addition of the host-guest complex affects the stacking of GO nanosheets to a certain extent, thus compensating for the wrinkles. Figure 3 As can be seen from the small figure (middle df), the two-dimensional layered structure of the membrane is obvious and the stacking is highly ordered. The thickness of the separation layer is relatively uniform. 2+ and CB6-Ba 2+ The addition of the host-guest complex increases the thickness of the film and greatly changes the curvature of the GO nanosheets, which will further affect the roughness of the film. 2+ Membrane and GO-CB6-Ba 2+ AFM images of the membrane ( Figure 3 This phenomenon is further confirmed by the small figure in the figure (inset in the middle). The image shows that all the intercalated GO membranes show a smoother membrane surface than the original membrane, and the roughness gradually decreases. The GO membrane exhibits the greatest roughness, which can be attributed to the local hydrogen bonding interaction between the large number of oxygen-containing functional groups on the GO nanosheets, causing some areas of the GO nanosheets to aggregate and form folds during the stacking process. 2+ and CB6-Ba 2+ The interaction between the complex and GO allows it to be inserted into the interlayer of GO nanosheets, which weakens the non-covalent bonding interaction between adjacent GO nanosheets, making them stacked uniformly and orderly in the pressure-assisted process, resulting in a flatter membrane surface structure. 2+ The roughness of the film is greater than that of GO-Ba 2+ The reason for this is that the intrinsic rigid structure of CB6 hinders the complete stacking of GO nanosheets.

[0061] During the experiment, the surface morphology of the GO membrane and GO-CB6 membrane prepared in Comparative Example 1 and Comparative Example 3 was observed. It was found that the surface of the GO-CB6 membrane showed agglomeration of GO nanosheets, resulting in defects on the membrane surface, which was caused by the uneven stacking of GO nanosheets. The cross-sectional image of the GO-CB6 membrane further proved this conclusion. The GO nanosheets were loosely and chaotically stacked, and the thickness was uneven. This proves that CB6 cannot be used alone as an interlayer crosslinker for GO nanosheets due to the lack of active sites. Therefore, CB6-Ba 2+ The intercalation of host-guest complexes has an extremely important effect on the microstructure of GO membranes.

[0062] The stacking of GO nanosheets will lead to changes in the membrane surface morphology and will also affect the formation of membrane channels. 2+ and CB6-Ba2+ The changes brought by intercalation to GO channels were characterized by XRD in dry and wet states. The Bragg equation was used to calculate the GO membrane, GO-Ba 2+ Membrane and GO-CB6-Ba 2+ The interlayer d-spacing value of the film ( Figure 4 (a) 2+ The introduction of CB6-Ba increases the interlayer spacing of GO, but 2+ The introduction of makes the GO interlayer spacing smaller. The d-spacing of the original GO membrane increases significantly from 1nm to 1.11nm. This is because in the wet state, the GO nanosheets have strong hydrophilicity due to the presence of oxygen-containing functional groups, so that water molecules are adsorbed into the interlayer channels, resulting in the swelling of the membrane structure. In contrast, GO-CB6-Ba 2+ The difference in the dry and wet d-spacing of the membrane is smaller than that of the pristine GO membrane, indicating that the CB6-Ba 2+ The interaction between water and GO improves the anti-swelling property of GO membrane. Using water molecules as probes, LF-NMR ( Figure 4 (B) Further analysis of CB6-Ba 2+ The effect of intercalation on the microscopic channel structure of the membrane. For the GO membrane structure, there will be three time domains, namely the sub-nanometer confinement area (10 -1 -10ms time domain area, channel I), nanometer-level confinement area (10-10 3 ms time domain region, channel II) and the free water region not in the GO membrane (10 3 -10 4 ms time domain region, channel III). Channel I belongs to the nanochannels generated by the interlayer spacing of the GO membrane, while channel II represents the microporous defects constructed by loosely overlapping GO nanosheets. 2+ Compared with the membrane, in the sub-nanometer confinement region, GO-CB6-Ba 2+ The relaxation time of water in the membrane increases, indicating that water molecules penetrate the GO interlayer spacing, diffuse more easily, and the interlayer spacing increases. 2+ The relaxation time of the membrane decreases within the nanoconfinement region, indicating a decrease in the size and number of microporous defects, which indicates that CB6 and Ba 2+ The addition of makes the GO nanosheets stacked more orderly and the channels more regular.

[0063] 3. OSN performance of membranes

[0064] 3.1 Solvent transfer

[0065] In order to verify the encapsulation of CB6-Ba 2+The intercalation of the complex can solve the swelling problem of GO. Experiments were carried out using solvents with different polarities. Before the OSN experiment, the stability of the membrane was evaluated by observing the apparent morphology of the membrane after ultrasound in water and measuring the weight loss ratio in different solvents.

[0066] GO membrane and GO-Ba 2+ After a period of ultrasound exposure, the GO selective layer on the membrane surface began to fall off. In contrast, GO-CB6-Ba 2+ The base film of the membrane showed good bonding with the selective layer, and the GO layer remained intact during subsequent tests. 2+ The membrane has smaller weight loss ratios in several solvents than the other two membranes.

[0067] See also Figure 5 In the middle a panel, compared with GO film and GO-Ba 2+ Membrane, GO-CB6-Ba 2+ The membrane showed better permeability to common solvents such as N,N-dimethylformamide (DMF), ethanol (EtOH), methanol (MeOH), water (Water), and acetonitrile (ACN). The introduction of CB6 significantly improved the membrane's permeability to solvents, especially the improvement in water and acetonitrile flux.

[0068] For GO-CB6-Ba 2+ The membrane's resistance to compaction in water and acetonitrile was evaluated and found to be ( Figure 5 (Fig. b), the water and acetonitrile fluxes increased linearly without slowing down, indicating that the membrane can withstand higher pressure. The possible reason is that GO-CB6-Ba 2+ The membrane has a larger interlayer spacing due to the addition of CB6, which accelerates the penetration of organic solvents. In addition, the rigid structure of CB6 may reduce the swelling degree of the membrane in organic solvents, thereby maintaining the structural stability of the channel and increasing the solvent permeability.

[0069] Further study the transport of solvents in membrane nanochannels to clarify the reasons for the increased permeability of solvents in the membrane. First, study the relationship between solvent properties and membrane permeability. The difference in solvent permeability may be related to the physical parameters of the solvent, such as viscosity, solubility parameters, kinetic diameter, etc. The experiment found that GO-CB6-Ba 2+ The membrane permeability is strongly correlated with the viscosity of the solvent ( Figure 5 The order of permeability to pure solvents is acetonitrile (27.23LMH bar -1 )>Water (11.69LMHbar -1 )>Methanol(8.61LMH bar -1)>Ethanol(3.52LMH bar -1 )>DMF(0.13LMH bar -1 ). Therefore, it can be shown that solvent viscosity plays an important role in the solvent permeation process of this membrane.

[0070] GO-CB6-Ba 2+ The rapid water permeability of the membrane is due to the adsorption of water molecules by the carbonyl groups on the CB6 molecules. By testing the surface Zeta potential of several membranes, the surface charge density σ( Figure 5 (D) Due to the hydrolysis of oxygen-containing functional groups on GO nanosheets, the GO membrane has a negatively charged surface, while Ba 2+ The addition of CB6 reduces the negative charge density on the membrane surface. 2+ The surface charge density of the membrane is comparable to that of the GO membrane, but its water permeability is nearly four times higher, indicating that the presence of the carbonyl port on CB6 enhances the hydrogen bonding interaction between it and water molecules, allowing water to easily adsorb on the membrane surface and penetrate rapidly. In addition, the dynamic water contact angle ( Figure 5 The three membranes have similar surface hydrophilicity, but at 2s, GO-CB6-Ba 2+ The decrease rate of the water contact angle of the membrane is greater than that of the GO membrane and GO-Ba 2+ The contact angles of the films decreased by 7.2%, 13.8% and 15.3% after 18s, indicating that water molecules entered the interlayer of the films faster. This indicates that the addition of CB6 molecules makes it easier for water molecules to enter the interlayer of GO nanosheets, which is beneficial for water molecules to penetrate into the main body of the membrane.

[0071] Low-field NMR using acetonitrile molecules as probes further demonstrated the transport of acetonitrile molecules in the channel ( Figure 5 (f) As can be seen from the figure, the GO film and GO-Ba 2+ Compared with the membrane, GO-CB6-Ba 2+ The relaxation time of ACN in the sub-nanometer confinement region of the film increases, indicating that ACN molecules penetrate the GO interlayer spacing and diffuse more easily (similar to the transport of water molecules). 2+ The relaxation time of the membrane decreases within the nanoconfinement region, indicating a decrease in the size and number of microporous defects, indicating that CB6 and Ba 2+ The addition makes the GO nanosheets stacked more orderly, the channels more regular, and the transmission path of acetonitrile molecules shortened, thereby increasing its permeability.

[0072] 3.2 Separation performance

[0073] The effects of different sized and charged solutes on GO-CB6-Ba 2+ The preliminary performance of the membrane was evaluated. 2+ The membrane has a higher retention rate for negatively charged dyes than for positively charged ones, and has a higher retention rate for dyes with a molecular weight above 600. 2+ The separation potential of the membrane in organic solvent systems was tested for the separation performance of several dyes in an acetonitrile system. The retention of the membrane for several dyes (Reactive Blue 19 (RB19), Aniline Blue (AB), Methyl Blue (MB), Fast Green (FG) and Coomassie Brilliant Blue (BBR)) was maintained above 90%, and the acetonitrile flux reached 25LMH bar. -1 above( Figure 6 (a, small figure).

[0074] At the same time, the long-term stability of Fast Green in acetonitrile was investigated ( Figure 6 (B) In the 110h test, GO-CB6-Ba 2+ The retention of fast green by the membrane was always kept above 99%, while the permeability decreased, which can be attributed to the adsorption of the dye on the membrane surface.

[0075] Compared with the OSN performance in the literature, GO-CB6-Ba 2+ The membrane exhibits good solvent permeability and molecular selectivity. The retention mechanism of the membrane for dye molecules can be attributed to size screening and Donan effect. According to the size and electrical properties of the dye molecules and the Zeta potential of the membrane, GO-CB6-Ba 2+ The membrane surface is negatively charged, so the membrane has an electrostatic repulsion effect on negatively charged dyes. At the same time, due to the membrane pore size and the size of the interlayer channels, it has different separation effects on molecules of different sizes.

[0076] The above study reveals the influence of intercalation complexes on the formation of GO membrane channels and provides a new GO intercalation material to improve the stability of GO membranes. This material is expected to be used for the intercalation of other two-dimensional material membranes.

[0077] The above shows and describes the basic principles, main features and advantages of the present invention. However, the above is only a specific embodiment of the present invention, and the technical features of the present invention are not limited thereto. Any other implementation methods derived by any technician in the field without departing from the technical solution of the present invention should be included in the patent scope of the present invention.

Claims

1. A two-dimensional nanochannel membrane regulated by molecular encapsulation technology, characterized in that: The invention comprises a substrate and a selective separation layer on the substrate, wherein the selective separation layer is composed of graphene oxide (GO) nanosheets, and a host-guest complex composed of cucurbituril encapsulating metal ions is provided between adjacent GO nanosheets.

2. The two-dimensional nanochannel membrane regulated by molecular encapsulation technology according to claim 1, characterized in that: The cucurbituril is one or more of CB6, CB7, CB8, CB9, and CB10; the metal ion is Ba 2+ , Ca 2+ or Cu 2 + One or more of the .

3. The two-dimensional nanochannel membrane regulated by molecular encapsulation technology according to claim 1, characterized in that: The substrate is a polyimide material.

4. The two-dimensional nanochannel membrane regulated by molecular encapsulation technology according to claim 1, characterized in that: The surface of the substrate is cross-linked with polyamine, and the polyamine is selected from one of triethylenetetramine, diethylenetriamine and polyethylenepolyamine.

5. The method for preparing the two-dimensional nanochannel membrane according to claim 1, characterized in that: The steps include: The metal ion salt and cucurbituril are dissolved in deionized water for encapsulation to form a host-guest complex solution, and a GO dispersion is added to obtain a coating solution. The coating solution is deposited on the modified substrate by a pressure-assisted filtration method to form a uniform coating layer, and a nanofiltration membrane is obtained after heat treatment.

6. The preparation method according to claim 5, characterized in that: The substrate is polyimide, which is firstly subjected to cross-linking treatment. The cross-linking treatment process is: immersing the PI substrate in polyethylene polyamine with a mass concentration of 8-15% for 10-20 minutes to complete the cross-linking.

7. The preparation method according to claim 5, characterized in that: The metal ion salt is Ba 2+ , Ca 2+ or Cu 2+ Salt, whose anion is Cl - 、NO3 - 、CO3 2- 、SO4 2- Any one of the following; the mass percentage of the metal ion salt in the host-guest complex solution is 0.2-0.5wt%, and the mass percentage of cucurbituril is 0.6-0.8wt%.

8. The preparation method according to claim 5, characterized in that: GO dispersion is prepared by dispersing GO solution in deionized water and ultrasonically treating it for 100 to 140 min. The concentration of GO in the obtained GO dispersion is 0.03 to 0.05 mg mL -1 ; The volume ratio of GO dispersion to host-guest complex solution is 10:1-2.5; 2 The amount of coating liquid used is 5-30mL on the surface of the base film of the same area.

9. Use of the two-dimensional nanochannel membrane according to claim 1 in filtering an organic solvent system.

10. The use according to claim 9, characterized in that: Organic solvent system filtration is aimed at filtering negatively charged, positively charged or neutral dyes; the nanofiltration membrane is used to improve permeation flux or molecular selectivity.

Citation Information

Patent Citations

  • A method for preparing and applying a cucurbituril / metal ion crosslinked graphene oxide composite membrane.

    CN112934004B

  • Solvent resistant polyimide membrane, preparation method and application

    CN108837715A

  • Nanofiber molecular sieve membrane, preparation method and application

    CN114522548A